Ensuring National Security under Martial Law Conditions: Legal Regulation, Threats, Cooperation and Directions for Improvement - Andrii Nosach; Sergii Melnyk; Anatolii Rusetskyi; Yuliia Pinchuk; Volodymyr Piadyshev (Khazanah Hukum)
The purpose of the article is to reveal the legal regulation of ensuring national security in the conditions of martial law (threats, cooperation and directions for improvement).  It has been established that ensuring national security of Ukraine includes a complex of national and international measures. It has been emphasized that financing is one of the important problems in the system of ensuring national security. The financial security of a state as a component of its national security is the basis of the economic development of the country, which ensures sovereignty and integrity of the country, as well as a decent standard of living of its citizens. The financial security of a state as a component of its national security is the basis of the economic development of the country, which ensures sovereignty and integrity of the country, as well as a decent standard of living of its citizens. Another problem of ensuring national security in wartime conditions consists in preventing and combating corruption.  Corruption destroys development of the military-industrial complex, prevents introduction of innovative means of protection for military personnel, it disturbs development and testing of new weapons, new technologies, and hampers provision of military personnel with the necessary equipment, protection and weapons. It was concluded that only cooperation can solve the urgent strategic tasks of ensuring national security in difficult world conditions and new globalization challenges.